Wrinkled stripes localized by cracks in metal films deposited on soft substrates1. Issue 11 (21st March 2015) - Yu, Senjiang; Zhang, Xiaofei; Xiao, Xiaofei; Zhou, Hong; Chen, Miaogen
<x xml:space="preserve">Abstract</x> Homogeneous wrinkling patterns such as labyrinths, herringbones and ripples can be widely observed in natural and artificial systems, but localized wrinkles (not delaminations, folds, ridges or creases) are seldom observed in experiments. Here we report on the spontaneous formation of highly ordered wrinkled stripes localized by cracks in metal films deposited on soft substrates.